2014
DOI: 10.1159/000369045
|View full text |Cite
|
Sign up to set email alerts
|

Germline DNA Variations in Breast Cancer Predisposition and Prognosis: A Systematic Review of the Literature

Abstract: Breast cancer is the most common cancer and the second leading cause of death in women worldwide. The disease is caused by a combination of genetic, environmental, lifestyle, and reproductive risk factors. Linkage and family-based studies have identified many pathological germline mutations, which account for around 20% of the genetic risk of familial breast cancer. In recent years, single nucleotide polymorphism-based genetic association studies, especially genome-wide association studies (GWASs), have been v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 142 publications
(233 reference statements)
0
23
0
3
Order By: Relevance
“…Breast cancer is a complex multifactorial disease, which results from an interplay of environmental, reproductive, lifestyle, and genetic risk factors . Canine cancers occur spontaneously, and have similar clinical presentation and pathophysiology to equivalent human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a complex multifactorial disease, which results from an interplay of environmental, reproductive, lifestyle, and genetic risk factors . Canine cancers occur spontaneously, and have similar clinical presentation and pathophysiology to equivalent human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of studies have been performed to investigate low-penetrance genetic susceptibility in female BC (FBC), and susceptibility alleles have been reported in about 70 loci widespread in the genome [21]. By contrast, only a few studies addressed the role of low-penetrance alleles in MBC susceptibility [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…21 BC-associated loci widespread in the genome, may influence the risk of BC in men, and whether they may be associated with specific clinical-pathologic characteristics of male BC (MBC).…”
mentioning
confidence: 99%
“…Data from almost 400,000 women affected with breast cancer showed that 281 SNPs are significantly associated with the risk of this disease, which reduced to 233 risk loci when linkage disequilibrium was taken into account. These findings add new information to the already existing recent literature reviews on this subject, which report up to 172 common variants linked to breast cancer susceptibility (3,4,6,(67)(68)(69)(70)(71). These SNPs are estimated to account 15-20% of the genetic component of disease risk (3,72), which clearly implies that much more work is needed to fully elucidate the molecular basis of breast cancer predisposition.…”
Section: Discussionmentioning
confidence: 53%